2011
DOI: 10.1136/thoraxjnl-2011-200089
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression networks in COPD: microRNA and mRNA regulation

Abstract: BackgroundThe mechanisms underlying chronic obstructive pulmonary disease (COPD) remain unclear. MicroRNAs (miRNAs or miRs) are small non-coding RNA molecules that modulate the levels of specific genes and proteins. Identifying expression patterns of miRNAs in COPD may enhance our understanding of the mechanisms of disease. A study was undertaken to determine if miRNAs are differentially expressed in the lungs of smokers with and without COPD. miRNA and mRNA expression were compared to enrich for biological ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
286
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(301 citation statements)
references
References 40 publications
13
286
1
1
Order By: Relevance
“…In stimulation experiments using endothelial cells that, in vivo, reflect the first responders of the lungs to these proinflammatory signals, we found that IL-1β and TNFα significantly induced the levels of miR-223 in a time-dependent manner. These cytokines have been described as key inflammatory mediators in COPD [2,3] and their activity in COPD patients might explain the significant upregulation of miR-223 levels in vivo as shown by Ezzie and colleagues [21]. Both cytokines are activators of the transcription factor nuclear factor kappa B (NF-κB).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In stimulation experiments using endothelial cells that, in vivo, reflect the first responders of the lungs to these proinflammatory signals, we found that IL-1β and TNFα significantly induced the levels of miR-223 in a time-dependent manner. These cytokines have been described as key inflammatory mediators in COPD [2,3] and their activity in COPD patients might explain the significant upregulation of miR-223 levels in vivo as shown by Ezzie and colleagues [21]. Both cytokines are activators of the transcription factor nuclear factor kappa B (NF-κB).…”
Section: Discussionmentioning
confidence: 96%
“…miRNAs have emerged as post-transcriptional gene silencers and we thus suggested their involvement in the decreased expression of HDAC2. In the context of COPD, miR-223 was recently described as the most upregulated miRNA in lung tissue of patients but its function has not been addressed [21]. Several miRNA target prediction algorithms identified potential binding sites of miRNAs that included seed matches for miR-223 in the 3'UTR of HDAC2 [18].…”
Section: Discussionmentioning
confidence: 99%
“…RCR was performed using Gene Expression Omnibus (GEO) COPD and emphysema data sets from lung, small airway, and alveolar macrophages of early COPD patients and healthy smokers (see Dataset) 5963 . RCR has been used previously to predict upstream regulators from transcriptomic data 8 .…”
Section: Methodsmentioning
confidence: 99%
“…Expression profiling of lung tissue from subjects with COPD and smokers without COPD has revealed 70 miRNAs that are differentially expressed, including miR-223, miR-127a, miR-424 and miR-15b [115]. The group concentrated on miR-15b and found that expression correlated with severity of COPD as assessed by spirometry [115].…”
Section: B-cellsmentioning
confidence: 99%
“…The group concentrated on miR-15b and found that expression correlated with severity of COPD as assessed by spirometry [115]. Interestingly, miR-15b was able to regulate components of the transforming growth factor (TGF)-b pathway, a key growth factor implicated in airway remodelling in COPD.…”
Section: B-cellsmentioning
confidence: 99%